MO-CCCCTA-Based Floating Positive and Negative Inductors and Their Applications - Neeta Pandey; Rishik Bazaz; Rahul Manocha (Journal of Electrical and Computer Engineering)
This paper introduces a floating inductance simulation using multiple output current controlled current conveyer transconductance amplifier (MO-CCCCTA). The simulated inductor retains minimum requirement of passive elements as only one-grounded capacitance is used for one inductor. PSPICE simulation has been done and included to ensure the validity of the approach. A few applications have also been included to substantiate the usability of the proposed circuit.